Evaluation of Suspected Adverse Drug Reactions of Oral Anti-diabetic Drugs in a Tertiary Care Hospital for Type II Diabetes Mellitus - Keezhipadathil, Jiji (Indian Journal of Pharmacy Practice)
Background and Objective: The objective of the study was to evaluate and analyse ADRs in type II diabetic patients and to determine the causality, severity and preventability of reactions. Methods: 460 diabetic patients on oral anti-diabetic drugs were evaluated prospectively over a period of six months. All patients were followed up for ADRs which were evaluated for incidence, frequency, severity and causality. Causality was graded according to WHO-UMC scale and Naranjo scale. Severity according to Modified Hartwig and Siegel scale and preventibility based on Modified Schumock and Thornton Scale. Results and Discussion: A total of 58 ADRs were reported from 460 patients during the study period with female predominance over male. All the ADRs that were reported were of type A category. The class of drug responsible for causing more ADRs was found to be biguanides. The most commonly affected organ system was GI System The suspected ADRs were assessed for their causality, it was revealed that 52 were probable and 6 were possible and as per Naranjo scale 53 were probable and 5 possible. The ADRs were assessed for severity using Modified Hartwig and Siegel scale and it was observed that 28 were mild and 30 moderate. Preventibility of reported ADR cases was assessed using the Modified Schumock and Thornton Scale. Using this scale all 58 ADRs were probably preventable. Conclusion: These study results provide insight to the healthcare providers on the importance of monitoring and reporting ADR associated with the drugs.
Keywords: Adverse Drug Reaction; WHO-UMC Scale; Naranjo Scale; Modified Hartwig and Siegel scale; Modified Schumock; Thornton Scale.